Long-Term Effects of the Harvesting of Trapa natans on Local Water Quality and Aquatic Macrophyte Community in Lake Erhai, China - Yuan, Changbo; Bai, Xiaohu; Zhu, Tianshun; Wen, Zihao; Cao, Te; Zhang, Xiaolin; Ni, Leyi (Frontiers in Environmental Science, 2021)
Trapa natans is one of the main species causing the swamping in the littoral zones of Erhai Lake. It commenly form dense canopy at water surface in the growing season (June to September), which hampers the local water quality and habitat of submerged macrophytes, and releases nutrients to the water after death in autumn and winter resulting in deterioration of local water quality. At present, there are many and positive researches on the short-term effects of harvesting water chestnut on water quality and aquatic plants, but long-term observation results are lacking. In response to the above problems, we studied responses of water quality and aquatic plant community to the removal of Trapa in littoral zone of a northern bay in Erhai from August 2014 to January 2017. This could be the first attempt to discover the long-term effects of floating-leaved vegetation management in freshwater ecosystem. The results showed that the artificial removal of Trapa significantly improved the local water quality in growing season, e.g. the concentrations of total nitrogen (TN), dissolved nitrogen (DN), total phosphorus (TP) and dissolved phosphorus (DP) in non – Trapa zone (NTZ) was much lower than the adjacent Trapa zone (TZ). And the biomass of aquatic macrophyte community (BAMC) was significantly accelerated in NTZ, up to the maximum value of about 21 kg/m2 in fresh weight. However, the indexes of the community in NTZ declined. Therefore, we suggested that although the removal of Trapa improved the water quality and increased the productivity of the aquatic plant community, it reduced the species diversity of the aquatic plant community in the long run. This is another issue that we need to pay attention to in the later management in Erhai Lake.